ENGAGING PATIENTS FOR PATIENT SAFETY: A QUALITATIVE STUDY ON HEALTHCARE RECIPIENTS’ PERSPECTIVES - Ekorini Listiowati; Amal Chalik Sjaaf; Anhari Achadi; Adang Bachtiar; Merita Arini (Indonesian Journal of Health Administration, 2023)
Background: Patient safety (PS) is a global priority for achieving quality healthcare. Although patient engagement (PE) is a crucial risk-reduction strategy, research on this subject in Indonesia is scarce. Aim: This study aims to explore healthcare recipients’ (HCRs’) perspectives and their potential role in PS. Methods: Exploratory qualitative research was conducted with in-depth interviews (IDIs). This study purposively selected fourteen patients and fifteen caretakers in chronic wards. Content analysis was subjected to the IDIs data that has been transcribed verbatim. Results: HCRs showed inadequate knowledge, perception, and willingness to engage in patient safety. Four themes were identified from data analysis: (1) complexity barriers to PE Implementation; (2) enabling factors for PE; (3) HCRs' expectations; and (4) existing and potential HCRs' roles in PS. HCRs' roles were still limited to communication, positive attitude and behavior, aided healthcare process, and error prevention. Conclusion: The limited roles of HCRs resulted from their unreadiness to participate more in PS. For patients to be engaged in safety measures, it was essential to improve the ability of patients and caregivers and eliminate obstacles encountered by healthcare professionals and the broader health system. Keywords: patient engagement, patient safety, quality healthcare